Effect of exercise intensity on shooting performance in the sport of summer biathlon - Higginson, B. (2002)
The purpose of this study was to determine the effect of running intensity on shooting performance in summer biathletes by comparing shooting scores immediately following bouts of exercise at four different intensities in an effort to determine if running intensity can be maintained, or increased, without a subsequent decrement in shooting performance. Each subject (seven elite and three novices) was required to shoot five shots at paper targets immediately following bouts of exercise at four different intensities. Exercise intensities included shooting with a resting heart rate (INT1), slowing to 75% of race pace (INT2), maintaining race pace (INT3), and sprinting (INT4). All subjects began testing by shooting five shots prone and five shots standing at INT1. All subsequent conditions were counterbalanced for intensity and position. A one kilometer loop was run between shooting bouts with changes in exercise intensity (INT2-INT4) occurring 50 meters prior to entering the range. Measures of shooting performance included the number of shots hit (SH), shooting accuracy (SA), and shooting precision (SP). As intensity increased from lNT2 to INT4, there was a significant decrease (p<.001) in 50 meter run time prior to entering the range (12.52 s vs. 8.96 s, respectively), with no difference in one kilometer run times (p=0.50). Although an increase in exercise intensity was associated with a decrease in SH for both the prone and standing position, there was no significant difference in SH for the elite subjects (N7), or all subjects as a group (N10), as a result of position (N7: p=0.64, N10: p=0.86) or intensity (N7:p=0.10, N10: p=0.12). A significant interaction effect was found in N7 for the SA measure of shooting performance (p=0.005), as well as a significant difference in both position (p<0.001) and intensity (p=0.008) for the SP measure. SA for N10 was significantly different for both position (p<0.001) and intensity (p=0.009). There was no difference between N7 and N10 for the SP measure of shooting performance. These preliminary findings indicate that race times may be decreased in the sport of summer biathlon by as much as 7.12 seconds in a 5 km race without a subsequent compromise in shooting performance.